Revenus et niveaux de bilinguisme écrit et oral : les hommes québécois en 1971 - Vaillancourt, François; Pes, Johanne (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThis paper examines the roles of second language oral and written skills in the determination of the earnings of a sample of Quebec men in 1971. A log-linear earnings equation is used with education and experience as additional independent variables. The main results are that it is preferable to measure language skills as precisely as possible and that both oral and written skills play a role in the earnings determination equation, but the former more so.